Predefining regionalised environments for assisted navigation : does incorporating regions into navigation instructions assist a user’s spatial understanding of the environment they aretravelling through? - Thorn, Caitlin Lara (2018)
Dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science in Geospatial Technologies